Pengaruh Promosi Penjualan Terhadap Online Customer Review serta Dampaknya pada Keputusan Pembelian di Sayurbox - Novan Yurindera (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
This study aims to examine the direct and indirect impact of promotions on purchasing decisions through Sayurbox's online customer reviews. The independent variable in this study was promotion, the dependent variable was purchase decision, and the intervening variable was online customer ratings. Quantitative data analysis uses the SEM method and the partial least squares (PLS) approach. It consists of an analysis of the external model followed by an analysis of the internal model, ending with hypothesis testing using the SmartPLS application. The results of this study show that promotions have a positive impact on online customer reviews, online customer reviews have a positive impact on purchasing decisions, and the end result is that promotions have a positive impact on online customer reviews through purchases, indicates that it has a direct and indirect positive impact on Decision making.